Comparison of raw meat quality and protein-gel properties of turkey breast fillets processed by traditional or cold-batter mincing technology. (18th January 2019) - Lee, H C; Singh, P; Strasburg, G M; Marks, B P; Jin, H W; Kang, I
ABSTRACT: This study was conducted to evaluate the effects of cold batter mincing on meat quality and protein functionality, using turkey fillets that were chill-boned (CB ) or hot-boned (HB ) with crust-freeze-air-chilling (HB-¼CFAC ) at −12°C. For each of four replications, 48 toms (male) were raised and processed at Michigan State University Poultry Farm and Meat Laboratory, respectively. After evisceration, the turkeys were subjected to one of the four treatments: (1) traditional mincing of CB fillets after water immersion chilling (WIC ); (2) cold batter mincing of WIC, CB, quarter-sectioned (¼), and CB-¼CFAC; (3) traditional mincing of HB-¼CFAC fillets; and (4) cold batter mincing of HB-¼CFAC fillets. Before mincing, the pH and R-values of turkey fillets in HB-¼CFAC were higher and lower, respectively, than those in CB fillets. During cold-batter mixing, the initial batter temperatures at −1.5 to −2.1°C reached 1.5°C and 14°C at 6 and 12 min, respectively, and ended at 26 to 31°C at 24 min. During traditional mincing, the initial batter temperatures at 3 to 4°C increased by ∼10°C every 6 min, and ended at 32 to 35°C with higher batter temperatures seen for the 2% salt than the 1% salt batter. Dynamic rheological properties indicated that the cold-batter mincing showed elevated G' compared to the batters of traditional mincing, regardless of mixing time, indicating that the gel-setting temperature was reduced in the cold-batter mincing, potentially due to the different amounts of extracted protein and structural change. After cooking, improved cooking yield and protein functionality were observed in the batter of HB-¼CFAC fillets than the batter of CB fillets as well as in the batter of 2% salt than the batter 1% salt ( P < 0.05). These results indicated that HB-¼CFAC fillets produced superior raw meat quality over the CB fillets, and cold batter mincing of HB-¼CFAC fillets significantly improved protein functionality compared with the traditional mincing of CB fillets ( P < 0.05).